Responsive and equitable health system - partnership on non-cimmunicable disease (RESPOND) study: a mixed methods, longitudinal observational study on treatment seeking for hypertension in Malaysia and the Philippines - Palafox, Benjamin; Seguin, Maureen L.; McKee, Martin; Dans, Antonio L.; Yusoff, Khalid; Candari, Christine J.; Idris, Khairuddin; Ismail, Johan Rizwal; Krauss, Steven Eric; Lasco, Gideon; Majid, Fadhlina A.; Villanueva, Lia M. Palileo; et al. (BMJ Publishing Group, 2018)
Introduction: Hypertension is a leading contributor to the global burden of disease. While safe and effective treatment exists, blood pressure control is poor in many countries, often reflecting barriers at the levels of health systems and services as well as at the broader level of patients’ sociocultural contexts. This study examines how these interact to facilitate or hinder hypertension control, taking into account characteristics of service provision components and social contexts. Methods and analysis: The study, set in Malaysia and the Philippines, builds on two systematic reviews of barriers to effective hypertension management. People with hypertension (pre-existing and newly diagnosed) will be identified in poor households in 24–30 communities per country. Quantitative and qualitative methods will be used to examine their experiences of and pathways into seeking and obtaining care. These include two waves of household surveys of 20–25 participants per community 12–18 months apart, microcosting exercises to assess the cost of illness (including costs due to health seeking activities and inability to work (5 per community)), preliminary and follow-up in-depth interviews and digital diaries with hypertensive adults over the course of a year (40 per country, employing an innovative mobile phone technology), focus group discussions with study participants and structured assessments of health facilities (including formal and informal providers). Ethics and dissemination: Ethical approval has been granted by the Observational Research Ethics Committee at the London School of Hygiene and Tropical Medicine and the Research Ethics Boards at the Universiti Putra Malaysia and the University of the Philippines Manila. The project team will disseminate findings and engage with a wide range of stakeholders to promote uptake and impact. Alongside publications in high-impact journals, dissemination activities include a comprehensive stakeholder analysis, engagement with traditional and social media and ‘digital stories’ coproduced with research participants.